Research report (2015)
This research study had as main objectives to identify participants’ perceptions about the four (4) areas of administration in the Tycoon Anno and at the same time to establish its strengths and weaknesses. In order to obtain such information, a qualitative-descriptive case study was carried out through coding frames and a survey applied to five (5) participants. Thanks to the research valuable results were found which aim at the existence of three (3) areas of administration and one (1) of these is not made evident. On the other hand relevant strengths and weaknesses were found, for those reasons it contributes to do recommendations at the end of the document.